Implementation of innovative technologies in Kazakhstan: A case of the energy sector. - Sitenko, D.; Gordeyeva, Ye.; Sabyrzhan, A.; Syzdykova, E. (Problems and Perspectives in Management, 2023)
The implementation of innovative renewable energy projects is designed to meet the growing electricity demand and reduce carbon dioxide emissions into the atmosphere. In order to avoid resource dependence of the economy and meet the demand for electricity in remote areas of Kazakhstan, the development of renewable energy sources is urgent. The purpose of this study is to analyze the effectiveness of the implementation of existing mechanisms for the implementation of innovative renewable energy projects through auctions. Moreover, it identifies their shortcomings and offers proposals for improvement. The analysis uses data from the Kazakhstan Bureau of National Statistics on renewable energy sources, namely alternative energy sources such as solar and wind power plants, excluding biogas. The methodology provides for the assessment of projects implemented through auctions for 2018–2021, taking into account such indicators as the dynamics of the number of wind and solar energy projects, their capacity, the percentage of auction price reduction for a specific year. The paper discusses the mechanism for conducting auctions of solar and wind electricity, which, through the auction organizer, connects authorized bodies and investors. The main indicators of auctions for individual years are noted, and the main shortcomings of this mechanism are identified. The analysis of barriers to innovative renewable energy project implementation revealed the presence of contradictions in the price regulation of renewable electricity, the lack of market pricing mechanisms, and the unpreparedness of the energy infrastructure for integration with renewable sources.
Keywords: renewable energy; innovation technologies; technology implementation; energy policy; auctions; barriers